Odpowiedzi

2013-08-08T22:34:28+02:00
a)\\5x^{2}=99-6x^{2}\\5x^2+6x^2
-99 = 0\\11x^{2}-99 =0\mid \div 11\\x^{2}-9=0\\(x-3)(x+3)=0\\x+3=0\vee
x-3=0\\x=-3\vee x=3  

b)\\x^{2}+169=0\\x^{2}=-169
kwadrat żadnej liczby rzeczywistej nie jest ujemny, dlatego równanie to nie ma rozwiązania  

c)\\x^{2}-\frac{4}{25}=0\\(x-\frac{2}{5})\cdotx(x+\frac{2}{5})=0\\x-\frac{2}{5}=0\vee
x+\frac{2}{5}=0\\x=\frac{2}{5}\vee x=-\frac{2}{5}  

d)\\x^{2}-1,2x=0\\x(x-1,2)=0\\x=0\vee
x-1,2=0\\x=0\vee x=1,2  

e)\\x^{2}=\frac{1}{2}\cdot
x\\x^{2}-\frac{1}{2}\cdot x=0\\x(x-\frac{1}{2})=0\\x=0\vee
x-\frac{1}{2}=0\\x=0\vee x=\frac{1}{2}  

f)\\(x-4)^{2}=9-8x\\x^{2}-8x+16=9-8x\\x^{2}-8x=9-16\\x^{2}=-7
kwadrat żadnej liczby rzeczywistej nie jest ujemny, dlatego równanie to nie ma rozwiązania    

g)\\(y+3)^{2}=3(2y+6)\\y^{2}+6y+9=6y+18\\y^{2}+6y+9-6y-18=0\\y^{2}-9=0\\(x-3)(x+3)=0\\x-3=0\vee
x+3=0\\x=3\vee x=-3